BENTUK DAN PERILAKU FRASA VERBA NOMINA DALAM BAHASA ARAB - Arifuddin, Arifuddin (CMES (Center of Middle Eastern Studies), 2017)
Verbal noun phrase (VNP) is a component of the construct phrase or idhāfah. This study aims to describe VNP’s structure and behavior in arabic grammar and show the unique characteristics of VNP among other types of construct phrase. The methodology used in this study is qualitative descriptive. The data containing VNP is collected from several sources i.e The Quran, Prophetic tradition, and online newspaper. The analysis of data is occurred by distributional methode in which bases its performance on analysing each linguistic particular related to other units. The results state that VNP has distinctive form: the first term mudhāf is a verbal noun which has neither the definite article nor nunation, and second term is definite or indefinite noun with no prepositional insertion. In order to syntac relation built by VNP the second term is the agent or doer of the action conveid by verbal noun, or the object of an action.